Confiabilidade estrutural de pilares existentes de concreto armado : influência da perda de armadura de aço e da idade do concreto - Luíza Cardoso Ribas e Castro (2019)
Concrete is a material of great impact in terms of sustainability. Around the world, a large volume of natural and economic resources is spent on the construction of structures and infrastructures in reinforced concrete, which generate waste when demolished. In addition, the sectors involved in the production and use of concrete emit between 5% and 10% of the carbon dioxide produced globally. Hence, the repair and rehabilitation of existing reinforced concrete structures are of great relevance, as it can reduce the use of natural resources and the generation of waste, as well as reducing costs. Therefore, the decision between rehabilitating or demolishing reinforced concrete structures should be guided by the analysis of the reliability of these structures. In the analysis of existing structures, it is necessary to consider the different pathologies that may affect the durability of reinforced concrete structures. In the context of mechanisms that cause degradation of reinforcement, corrosion is the main agent causing structural problems throughout the structure’s service life. Due to the formation of corrosion products, there is a loss of cross-sectional area of the reinforcing bars, which leads to a reduction in the resistant capacity and the safety levels of the structural elements. It should also be noted that the analysis of existing structures requires a different approach to that for new structures, especially with regard to the definition of target reliability levels. In view of the above, the present study aims to assess the reliability levels associated with existing short columns of reinforced concrete, subjected to axial load, with loss of the cross-sectional area of the longitudinal reinforcement. The probabilities of failure were obtained via Monte Carlo Simulation and the effects of different parameters were investigated. The analyses included 486 column models, considering the variation of the following parameters: number of specimens, the compressive strength of concrete and its coefficient of variation, the load ratio, which is given by the ratio between dead and live loads, the longitudinal reinforcement ratio, and the loss of the cross-sectional area of steel. The impact of age on the compressive strength of concrete was also investigated through the analysis of 243 column models. From the analysis of the explored scenarios, it was observed that all the investigated parameters have a significant impact on the reliability levels, especially the values of the compressive strength of concrete and its coefficient of variation.